Physiological changes and dna damage repair in arctic and antarctic Pseudogymnoascus spp. in response to ultraviolet-B radiation / Wong Hao Jie - Wong, Hao Jie (2019)
Solar radiation drives almost all biological activities on Earth and regulates the morphology of many organisms as well as their biochemical and developmental processes. Soil microorganisms such as fungi within the polar regions can be continuously exposed to considerable solar UV radiation in the summer. Prolonged exposure to UV radiation can cause DNA damage and negatively affect cellular and physiological processes such as transcription, growth and reproduction. Physiological and cellular responses of four polar fungal strains of Pseudogymnoascus spp. (HND16 R2-1 sp.2 and HND16 R4-1 sp.1 isolated from Hornsund, Svalbard in the Arctic; AK07KGI1202 R1-1 sp.3 and AK07KGI1202 R1-1 sp.4 isolated from King George Island in maritime Antarctica) toward UVB radiation were examined. All strains were identified through BLAST and phylogenetic analysis using three DNA markers comprising ITS, LSU and MCM7. Phylogenetic analysis indicates that all the strains are closely related and formed a cluster that is a mixture of clades A, B and C of genus Pseudogymnoascus, despite being isolated from the opposite poles. The first part of this study was to determine the physiological responses of the fungi, including growth, pigmentation, and conidia production, toward UVB exposure over a period of 10 days. UVB radiation was supplied with a daily dosage of 6.1 kJ m-2 d-1 in a 12/12 h day/night cycle of PAR at 15°C. All strains showed significant growth rate reduction between 22 and 35% when compared to controls. Pigment production was not induced throughout the 10-day exposure to UV-B radiation. Based on scanning electron microscope imaging, UVB radiation exposure inhibited conidia production in all the Pseudogymnoascus strains except for HND16 R4-1 sp.1. The aim of the second part of this study was to compare the repair pathway of UV-induced DNA damage under two repair conditions: (i) light condition that induces photoreactivation (Phr) and (ii) and dark condition that induces nucleotide excision repair (NER) pathways. Two types of DNA damage, namely cyclobutane pyrimidine dimers (CPDs) and pyrimidine 6-4 pyrimidone photoproducts (6-4PPs) were quantified using ELISA during repair incubation at 0, 2, 6, and 10 hours. Results showed that Antarctic strains were more resistant to UVB-induced CPD compared to Arctic strains, with CPD concentration being three-fold lower in the former strains. CPDs were repaired significantly faster in light than in dark conditions. For 6-4PPs, their repair rates were not significantly different between the two conditions. The expression of two DNA repair genes, RAD2 and PHR1 (each encoding a protein in NER and Phr, respectively) during the repair duration of 0 and 2 hours in the two different repair conditions were then measured using qPCR to determine the principal DNA repair pathway. The expression of PHR1 was downregulated and RAD2 was upregulated after UVB exposure in both light and dark repair conditions. However, the expression of PHR1 was induced by light without UVB radiation, suggesting the expression of PHR1 can be promoted in the presence of light. These observations suggest that the Phr pathway may not be involved in the repairing of UVB-induced DNA damage in Pseudogymnoascus, and that PHR1 may carry out a different function in these fungi. The difference in RAD2 expression between the two repair conditions was insignificant, suggesting an alternative repair mechanism may be involved in the repairing of CPDs in the presence of light. Findings from this study clearly demonstrate the effects of UVB irradiation on the growth and the reproduction of Pseudogymnoascus sp., suggesting the potential impact of increased UV radiation on the ecosystem functions of polar soil fungi, such as in the Arctic and Antarctic. In addition, this study provides some insights on the DNA repair mechanisms employed by these polar fungi to mitigate UV-induced DNA damage, on which studies were lacking previously in polar fungi.